Nuclear and non-nuclear analytical techniques applied to pre-colonial archaeological ceramics from the upper Madeira River/Brazil (940 to 760 B.P) (Brazilian Journal of Radiation Sciences, 2023)
This article presents the results of applying three archaeometric techniques in archaeological ceramics from the upper river Madeira region in Amazonia. The first consists of the nuclear technique, neutron activation analysis (INAA), to identify the trace elements of the clay sources used in the production of the vessels. The second, non-nuclear X-ray diffraction (XRD), was used to characterise the mineral phases of each clay source. The third technique, electron paramagnetic resonance spectroscopy (EPR), estimated burning temperature related to the production stage of the artefacts. This approach made it possible to understand technological choices linked to selecting specific clay sources. The results suggest that different indigenous groups that inhabited the region between 940 and 760 B.P selected three clay sources to produce their vessels.